Designing a ‘Fit-for-Purpose’ Approach to Tracking Progress on Climate Change Adaptation and Resilience: Learning from Local Governments in Australia. - Moloney, Susie; McClaren, Heather (Springer, 2018)
Local governments are at the forefront of responding to climate change in developing risk assessments and mitigation and adaptation strategies. In the Australian context, local government plans and strategies are emerging, however the extent to which municipalities are planning effectively for climate change and whether they are delivering on outcomes is difficult to assess. While there are a number of frameworks for monitoring, evaluating and reporting climate change adaptation and urban resilience, very few have been implemented at the local scale. This paper will present a case study from a group of councils in metropolitan Melbourne who have collaborated to develop a ‘fit-for-purpose’ framework to track how well they are adapting to climate change and to improve their resilience. The project process, framework design, indicators and pilot implementation phase will be outlined including an analysis of the challenges and issues that emerged in developing and implementing an approach to monitoring and evaluation. We seek to contribute to the gap in knowledge around ‘doing adaptation’ in particular how we can monitor and evaluate progress. In the post Paris climate policy context, much more attention is needed on how we can better understand the “actual experience of adaptation” which broadly asks “are we adapting”? (Ford and King in Mitig Adapt Strat Glob Change 20:505–526, 2015) and in the case of the particular Australian case study presented in this paper, the focus is on how can we assess ‘How Well Are We Adapting?’
Keywords: Stadtentwicklung; Klimawandel; Klimaanpassung; Resilienz; Stadtplanung; Planungsentscheidung; Evaluation; Fallstudie